Application of an acoustic emission source-tracing method to visualise shear banding in granular materials. Issue 10 (21st October 2021) - Lin, Wenli; Mao, Wuwei; Liu, Ang; Koseki, Junichi
Abstract : The acoustic emission (AE) technique can be used to locate failure-induced AE sources and provides an alternative to continuously visualise the development of failures inside stressed materials; however, a literature review reveals almost no studies regarding its application for source location in granular materials. Yet the visualisation of ubiquitously observed strain localisation and shear banding is critical to an in-depth understanding of the progressive failure mechanism of granular materials. In this paper, an original AE source three-dimensional (3D) tracing code based on the idea of 'time difference of arrival' (TDOA) was developed using Matlab programming, for the first time, to continuously visualise particle-scale interactions involved in saturated granular soils. After validating its feasibility through a series of pencil lead break (PLB) tests, the developed AE source 3D tracing code was applied to saturated granular soils subjected to drained triaxial shearing. Both the results of PLB tests and drained triaxial shearing tests demonstrate a good consistency between the traced AE source and actual PLB/particle interaction-induced sources. This suggests that the developed AE source 3D tracing code could be used to visualise the initiation and evolution of strain localisation and shear banding in saturated granular soils subjected to drained triaxial shearing.